Therapeutic Characterization and Efficacy of Bacteriophage Cocktails Infecting Escherichia coli, Klebsiella pneumoniae, and Enterobacter Species - Manohar, Prasanth; Tamhankar, Ashok J.; Lundborg, Cecilia Stalsby; Nachimuthu, Ramesh (Frontiers in Microbiology, 2019)
Infections due to antibiotic resistant bacteria are increasing globally and this needs immediate attention. Bacteriophages are considered an effective alternative for the treatment of bacterial infections. The aim of this study was to isolate and characterize the bacteriophages that infect Escherichia coli, Klebsiella pneumoniae and Enterobacter species. For this, clinical bacterial isolates of the mentioned species were obtained from diagnostic centers located in Chennai, Tamil Nadu, India. The bacteriophages were isolated from sewage water samples collected from Tamil Nadu, India. Phage isolation was performed using the enrichment method and agar overlay method was used to confirm the presence of bacteriophages. All the phages were characterized for their life cycle parameters, genome analysis and in vitro phage cocktail activity. The three bacteriophages exhibited broad host range activity: Escherichia virus myPSH2311 infecting E. coli belonging to six different pathotypes, Klebsiella virus myPSH1235 infecting K. pneumoniae belonging to four different serotypes and Enterobacter virus myPSH1140 infecting four different species of Enterobacter. Morphological observations suggested that the bacteriophages belonged to, Phieco32virus (Escherichia virus myPSH2311), Podoviridae (Klebsiella virus myPSH1235) and Myoviridae (Enterobacter virus myPSH1140). The life cycles (adsorption, latent period and cell burst) of Escherichia virus myPSH2311, Klebsiella virus myPSH1235 and Enterobacter virus myPSH1140 were found to be 26 min, 40 min and 11 min respectively. Genomic analysis revealed that Escherichia virus myPSH2311 is closely related to Escherichia phage vB_EcoP_SU10, Klebsiella virus myPSH1235 is closely related to Klebsiella phage vB_KpnP_KpV48 and Enterobacter virus myPSH1140 is closely related to Enterobacter phage PG7 and Enterobacter phage CC31. When phage cocktail was used against multiple bacterial mixtures, there was a reduction in bacterial load from106 CFU/mL to 103 CFU/mL within 2 hours. All the three characterized phages were found to have a broad host range activity and the prepared phage cocktails were effective against a mixed bacterial population that is resistant to meropenem and colistin, two last resort antibiotics. Infections caused by drug resistant bacteria will be a serious threat in the future and the use of virulent bacteriophages in therapy may offer an effective solution.